2005
DOI: 10.1111/j.1752-7325.2005.tb02807.x
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Meal, Snack, and Daily Total Food and Beverage Exposures on Caries Experience in Young Children

Abstract: Dietary methods used to investigate diet-caries relationships can influence the outcome. The cariogenicity of food, but not beverages, is associated with the timing of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
116
5
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 22 publications
12
116
5
13
Order By: Relevance
“…Foods rich in semi-hydrolyzed starch consumed between meals showed a significant association with great- er caries experience in this study; other authors [Marshall et al, 2005] have also encountered this association. Foods containing starch and sugar are more cariogenic than foods that only contain sugar.…”
Section: Discussionsupporting
confidence: 53%
“…Foods rich in semi-hydrolyzed starch consumed between meals showed a significant association with great- er caries experience in this study; other authors [Marshall et al, 2005] have also encountered this association. Foods containing starch and sugar are more cariogenic than foods that only contain sugar.…”
Section: Discussionsupporting
confidence: 53%
“…5,14 The majority of studies that investigated whether there is a relationship between snacking behaviour and weight status either found no association or found evidence indicating that young people who more often consumed food or beverages between meals were less likely to be obese. 36,37 Furthermore, Marshall et al 35 in 2005 showed a higher frequency of snacking among thin and normal weight children than obese children, and found that higher exposure to sugar from snacks increased caries risk than exposure to food sugar at mealtime. Perhaps overweight children consume more fatty foods, but fewer high sugary foods than normal weight children.…”
Section: Discussionmentioning
confidence: 99%
“…34 Other investigations, however, have reported an association between high weight and caries in the primary dentition. 14,35 It is difficult and complex to speculate on the mechanism by which obesity and dental caries were not associated, as it is well known that the high consumption of refined carbohydrates can be related both to the development of dental caries and obesity 16,33 . One way to explain the negative association between overweight and dental caries is the relationship between habits concerning main meals and snacks.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of DMFS and defs score was more among children who asked for the purchase of advertised products (sweets, foods, soft drinks). Marshall et al, identified that on average, young people spend 6.5 hours a day interacting, often multitasking, with various forms of media, and the majority of time is spent with television and music [7]. Pine et al, revealed that fruits, vegetables, proteinrich foods (i.e.…”
Section: Discussionmentioning
confidence: 99%